Exercise training for patients with type 2 diabetes and cardiovascular disease: What to pursue and how to do it. A Position Paper of the European Association of Preventive Cardiology (EAPC). (29th August 2020) - Kemps, Hareld; Kränkel, Nicolle; Dörr, Marcus; Moholdt, Trine; Wilhelm, Matthias; Paneni, Francesco; Serratosa, Luis; Ekker Solberg, Erik; Hansen, Dominique; Halle, Martin; Guazzi, Marco
Abstract: Patients with type 2 diabetes mellitus suffer from dysregulation of a plethora of cardiovascular and metabolic functions, including dysglycaemia, dyslipidaemia, arterial hypertension, obesity and a reduced cardiorespiratory fitness. Exercise training has the potential to improve many of these functions, such as insulin sensitivity, lipid profile, vascular reactivity and cardiorespiratory fitness, particularly in type 2 diabetes mellitus patients with cardiovascular comorbidities, such as patients that suffered from an acute myocardial infarction, or after a coronary intervention such as percutaneous coronary intervention or coronary artery bypass grafting. The present position paper aims to provide recommendations for prescription of exercise training in patients with both type 2 diabetes mellitus and cardiovascular disease. The first part discusses the relevance and practical applicability of treatment targets that may be pursued, and failure to respond to these targets. The second part provides recommendations on the contents and methods to prescribe exercise training tailored to these treatment targets as well as to an optimal preparation and dealing with barriers and risks specific to type 2 diabetes mellitus and cardiac comorbidity.